Role of Antibodies against Bordetella pertussis Virulence Factors in Adherence of Bordetella pertussis and Bordetella parapertussis to Human Bronchial Epithelial cells - van den Berg, Bernard M. (American Society for Microbiology, 1999)
Immunization with whole-cell pertussis vaccines (WCV) containing heat-killed Bordetella pertussis cells and with acellular vaccines containing genetically or chemically detoxified pertussis toxin (PT) in combination with filamentous hemagglutinin (FHA), pertactin (Prn), or fimbriae confers protection in humans and animals against B. pertussis infection. In an earlier study we demonstrated that FHA is involved in the adherence of these bacteria to human bronchial epithelial cells. In the present study we investigated whether mouse antibodies directed against B. pertussis FHA, PTg, Prn, and fimbriae, or against two other surface molecules, lipopolysaccharide (LPS) and the 40-kDa outer membrane porin protein (OMP), that are not involved in bacterial adherence, were able to block adherence of B. pertussis and B. parapertussis to human bronchial epithelial cells. All antibodies studied inhibited the adherence of B. pertussis to these epithelial cells and were equally effective in this respect. Only antibodies against LPS and 40-kDa OMP affected the adherence of B. parapertussis to epithelial cells. We conclude that antibodies which recognize surface structures on B. pertussis or on B. parapertussis can inhibit adherence of the bacteria to bronchial epithelial cells, irrespective whether these structures play a role in adherence of the bacteria to these cells.